Two new polyacetylene glycosides from the roots of Codonopsis tangshen Oliv. Issue 20 (17th October 2016) - Sun, Jiayou; Wang, Lun; Wang, Mingkui; Wang, Zhizhong; Li, Fu
Abstract: Two new polyacetylene glycosides, tangshenyne A (1 ) and tangshenyne B (2 ), along with six known polyacetylenes were isolated from an 85% MeOH extract of the roots of Codonopsis tangshen Oliv. The chemical structures of the new compounds were determined on the basis of extensive spectroscopic analyses, including UV, IR, 1D and 2D NMR ( 1 H– 1 H COSY, HSQC and HMBC) and HR-ESI-MS. Abstract :